Imobilisation of alkali treated apricot shells as a biosorbent for heavy metals removal - Šoštarić, Tatjana; Petrović, Marija; Lopićić, Zorica; Petrović, Jelena; Milojković, Jelena; Mihajlović, Marija; Stojanović, Mirjana (Journal of Engineering & Processing Management, 2017)
In this work, the design and usage of biosorbents made of apricot shells (Prunus armeniaca L.), Na-alginate and bentonite, for heavy metals removal from wastewaters, were investigated. The effect of particle size on the biosorption process, were investigate and the smallest fraction, was immobilized in Na-alginate. Immobilization had a positive effect on the biosorption process, but due to the inhomogeneity of the granules, bentonite was added as a binding agent. The result was increase of Cu(II) and Zn(II) removal up to 35% and Pb(II) up to 60. The composed granules were used for real effluent treatment. Obtained results indicated that this kind of composite biosorbent can be used in treatment of effluents contaminated with heavy metals pollution.